OPTIMALISASI APLIKASI DATA INFORMASI PENERBANGAN UNIT FLIGHT SERVICE STATION DI PERUM LPPNPI CABANG BALIKPAPAN - Muhamad Sahrul Romadh; Meita Maharani Sukma; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The safety factor is a major factor in the world of aviation. Not only that, in addition to flight safety, there are several other factors that support the development and growth in the aviation world. Among them are factors of speed and work efficiency. This is directly proportional to the increasing number of aircraft traffic every year so that efficiency in work is needed. Efficiency does seem trivial, but the impact caused if efficiency is not implemented is very vital. If efficiency in coordination is not realized, it can cause a Break of Coordination, so that it can cause complaints from other parties to Perum LPPNPI Balikpapan Branch. The method used in this paper is a qualitative descriptive research method that uses 2 variables; The effect of providing information data in the Flight Service Station unit (Variable X) and flight traffic services (Variable Y). Data collection techniques using; observations, questionnaires, and interviews. The result of this research is the creation of a special web application at the flight service station unit to support personnel efficiency when relaying an estimate to adjacent adjacent units and personnel are expected to always use the application during daily service. In addition, the author also recommends that the supervision socialize the use and operation of the web application to all Aeronautical Communication Officer (ACO) personnel at Perum LPPNPI Balikpapan Branch.